Liver Laceration from a Diaphragmatic Suture in Minithoracotomy Mitral Valve Repair. Issue 4 (18th April 2014) - Hashim, Peter W.; Hashim, Sabet W.
Abstract Mitral valve operations are increasingly performed through minimally invasive approaches such as the right anterior minithoracotomy. To facilitate exposure with this technique, a diaphragmatic suture may be implemented. We describe a liver laceration caused by the diaphragmatic suture in minithoracotomy mitral repair and its successful nonoperative management with arterial embolization. doi: 10.1111/jocs.12346 (J Card Surg 2014;29:476–477)